2022
DOI: 10.1002/cl2.1216
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to increase youth employment: An evidence and gap map

Abstract: Background: Globally, 13% of the youth are not in education, employment or training (NEET). Moreover, this persistent problem has been exacerbated by the shock of Covid-19 pandemic. More youth from disadvantaged backgrounds are likely unemployed than those from better off backgrounds. Thus, the need for increased use of evidence in the design and implementation of youth employment interventions to increase effectiveness and sustainability of interventions and outcomes. Evidence and gap maps (EGMs) can promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Similarly, it has been suggested that there is an overall skills mismatch of over sixty percent among employed youths, with critical deficiencies in a number of aspects such as critical thinking, entrepreneurial and technical abilities. The suggestion appears to be consistent to other revelations from similar studies, such as Mugabi et al (2021) and Apunyo et al (2022). The extent of poverty in the less-developing world is further supported by the fact that a good number of young people in Uganda are unemployable.…”
Section: Introductionsupporting
confidence: 86%
“…Similarly, it has been suggested that there is an overall skills mismatch of over sixty percent among employed youths, with critical deficiencies in a number of aspects such as critical thinking, entrepreneurial and technical abilities. The suggestion appears to be consistent to other revelations from similar studies, such as Mugabi et al (2021) and Apunyo et al (2022). The extent of poverty in the less-developing world is further supported by the fact that a good number of young people in Uganda are unemployable.…”
Section: Introductionsupporting
confidence: 86%
“…Job matching is among the most promising approaches to address the youth employment challenge. Indeed, the literature shows that effective job-matching interventions lead to better employment and earnings outcomes (Apunyo et al 2022, Generation Unlimited 2018, ILO 2020a, Sing and Liu 2020, J-PAL 2018.…”
Section: What Work In Youth Job Matching?mentioning
confidence: 99%
“…Globally, 13% of young people belong to the not in education, employment or training (NEET) category (Apunyo et al, 2022). This means that they are unemployed or inactive and not receiving any formal or non-formal education or training in a given period (Elder, 2015;Eurostat, 2022).…”
Section: Introductionmentioning
confidence: 99%